Effect of Multi-walled Carbon Nanotube Dispersion on the Electrical, Morphological and Rheological Properties of Polycarbonate/Multi-walled Carbon Nanotube Composites - Han, Mi Sun; Lee, Yun Kyun; Kim, Woo Nyon; Lee, Heon Sang; Joo, Jin Soo; Park, Min; Lee, Hyun Jung; Park, Chong Rae (POLYMER SOC KOREA, 2009)
The effect of a multiwalled carbon nanotube (MWCNT) dispersion on the electrical, morphological and rheological properties of polycarbonate (PC)/MWCNT composites was investigated, with and without pretreating the MWCNTs with hydrogen peroxide oxidation and lyophilization. The resulting PC/treated MWCNT composites showed higher electrical conductivity than the PC/untreated MWCNT composites. The morphological behavior indicated the treated composites to have greater dispersion of MWCNTs in the PC matrix. In addition, the electromagnetic interference shielding efficiency (EM I SE) of the treated composites was higher than that of the untreated ones. Rheological studies of the composites showed that the complex viscosity of the treated composites was higher than the untreated ones due to increased dispersion of the MWCNTs in the PC matrix, which is consistent with the electrical conductivity, EMI SE and morphological studies of the treated composites. The latter results suggested that the increased electrical conductivity and EMI SE of the treated composites were mainly due to the increased dispersion of MWCNTs in the PC matrix.
Keywords: CONDUCTIVITY; BLENDS